Expenditure Patterns of The Poor In Central Sulawesi - Meity Ferdiana Paskual; Santi Yunus; Nuryana Haprin; Failur Rahman (Eduvest - Journal of Universal Studies, 2022)
Eradication of poverty is one of the SDG's Goals. Increase in regional income and economic growth of Central Sulawesi has continued to occur in the last 5 years. However, Central Sulawesi still has poverty rates above the national average and relatively higher than other regions. Permendagri No. 53 of 2020 notes that one of the strategies related to poverty reduction is reducing the burden of spending on the poor. This study aims to explain how poor people allocate their expenditures. So it is hoped that it can add alternative regional poverty reduction policies. The data used is household expenditure data with the criteria below the Central Sulawesi Poverty Line. The database is sourced from raw data Susenas 2020. This study analyzes spending patterns, both food and non-food consumption components of the poor. The results showed that the consumption pattern of the poor was relatively larger for food consumption, namely 64 percent compared to non-food consumption at 36 percent. As for the details of the 5 largest food and non-food expenditure components, there are the Housing and Household Facilities component, the Grain component, the Prepared Food and Beverage component, the Miscellaneous Goods and Services component and the Cigarette and Tobacco component. This study recommends the interventions to reduce regional poverty through assistance in reducing the expenditure burden of the poor based on their needs according to the results of the study.